Forsythia suspensa extract enhances performance via the improvement of nutrient digestibility, antioxidant status, anti-inflammatory function, and gut morphology in broilers - Long, S.F. (Poult Sci, 2020)
This experiment aims to determine the effects of Forsythia suspense extract (FSE) as an antibiotic substitute on performance, antioxidant status, anti-inflammatory function, intestinal morphology, and meat fatty acid deposition in broilers. 192 male Arbor Acre broilers (1-day-old, weighing 45.6 ± 1.3 g) were randomly allocated to 3 treatments, 8 replicate pens per treatment, 8 broilers per pen. The treatments contain a control diet (corn-soybean meal basal diet, CTL), an antibiotic diet (basal diet + 75 mg/kg chlortetracycline, CTC), and an FSE diet (basal diet + 100 mg/kg FSE; FSE). The experiment includes phase 1 (day 1 to 21) and 2 (day 22 to 42). Compared with CTL and CTC, broilers supplemented with FSE showed higher (P < 0.05) ADG and ADFI in phase 2 and overall (day 1 to 42). On day 21, serum catalase and total antioxidant capacity contents were enhanced (P < 0.05) in broilers fed FSE compared with CTL. On day 42, broilers fed FSE showed increased (P < 0.05) serum superoxide dismutase and glutathione peroxidase contents, and enhanced (P < 0.05) apparent total tract digestibility of dry matter, organic matter, gross energy, total carbohydrates, and phosphorus, as well as reduced (P < 0.05) nitrogen and phosphorus excretion in feces compared with CTL. These broilers also showed decreased (P < 0.05) n-6/n-3 polyunsaturated fatty acid ratio in thigh meat, and tumor necrotic factor-alpha, interleukin-1β and interleukin-6 contents in the liver on day 42 compared with CTL. The villus height was increased (P < 0.05) in the duodenum, jejunum, and ileum of broilers fed FSE compared with CTL. In conclusion, dietary F.suspense extract supplementation as a chlortetracycline substitute under non-challenge conditions enhanced performance via the improvement of nutrient digestibility, antioxidant status, anti-inflammatory function, and intestinal morphology in broilers. Moreover, F.suspense extract may also benefit environment by reducing nitrogen and phosphorus excretion and benefit human health via modulating meat fatty acid profiles in broilers.